COMMUNITY SERVICE VILLAGE DEVELOPMENT PARTNER PKM- PDM WASTE INDEPENDENT VILLAGE IN KELING JEPARA VILLAGE - Rita Kartika Sari; Andhika Dwi Anggara; Novi Marlyana; Setyo Trisnadi (Jurnal Health Sains, 2023)
Background: Breast milk is also an important source of energy and nutrients during illness, and reduces mortality among malnourished children. Breastfeeding is a physiological process to provide nutrition to the baby optimally. To review evidence related to factors that influence the success of exclusive breastfeeding for working mothers. In Scoping review using the framework from Arksey and O'Malley, which focuses reviews with the PEOS framework, conducts literature searching using relevant databases and gray literature, selects relevant studies using inclusion and exclusion criteria, conducts critical appraisal for article quality assessment, conducts data extraction, analyzes and can report results. There were 8 articles selected and received Grade A. 8 articles were obtained research conducted in developing countries. There are 7 factors that affect the success of exclusive breastfeeding for working mothers, namely knowledge, educational status, breastfeeding facilities, employment status, husband support, family support, and health worker support.